2022
DOI: 10.3389/fimmu.2022.873054
|View full text |Cite
|
Sign up to set email alerts
|

ACT001 Inhibits TLR4 Signaling by Targeting Co-Receptor MD2 and Attenuates Neuropathic Pain

Abstract: Neuropathic pain is a common and challenging neurological disease, which renders an unmet need for safe and effective new therapies. Toll-like receptor 4 (TLR4) expressed on immune cells in the central nervous system arises as a novel target for treating neuropathic pain. In this study, ACT001, an orphan drug currently in clinical trials for the treatment of glioblastoma, was identified as a TLR4 antagonist. In vitro quenching titrations of intrinsic protein fluorescence and saturation transfer difference (STD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…We found that ACT001 treatment reduced IL-6 expression on mRNA and protein levels in sepsis mice ( Figure 7 ). This is consistent with results from other disease models ( Patel et al, 2019 ; Zhang et al, 2022 ). It also decreased TNF-α in serum, suggesting ACT001 may ameliorate cytokine storm in sepsis mice.…”
Section: Discussionsupporting
confidence: 93%
“…We found that ACT001 treatment reduced IL-6 expression on mRNA and protein levels in sepsis mice ( Figure 7 ). This is consistent with results from other disease models ( Patel et al, 2019 ; Zhang et al, 2022 ). It also decreased TNF-α in serum, suggesting ACT001 may ameliorate cytokine storm in sepsis mice.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of TLR4/P65 pathway has been confirmed to promote the progression of AS by triggering inflammatory response. Previous studies have confirmed that MCL/ACT001 can inhibit the activation of TLR4/P65 pathway [ 54 , 57 ]. Our data also showed that MCL reduced serum levels of inflammatory factors.…”
Section: Discussionmentioning
confidence: 78%
“…[5][6][7][8] Upon binding of agonistic ligands to MD2, it results in the formation of TLR4/MD2 dimerization, initiating the recruitment of the intracellular adaptor Toll/ Interleukin-1 receptor (TIR) domain and subsequently activating the downstream signaling pathway. 9 Dysregulation of the TLR4 signaling pathway can lead to numerous pathological conditions, including chronic inflammation, 10 asthma, 11 neuropathic pain, 12,13 etc. In addition, recent studies have indicated that psychoactive substances, including morphine, 14,15 cocaine, 16 and methamphetamine, 17 can activate TLR4/MD2 to enhance reward signaling, therefore contributing to drug addiction.…”
Section: Introductionmentioning
confidence: 99%